The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1309/0864af2u3lgpcf3j
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Vascular Endothelial Growth Factor Are Associated With Tumor-Associated Macrophages in Primary Breast Cancer

Abstract: We analyzed serum and tumor samples from 133 patients with operable primary breast cancer to determine the possible relationship between presurgery and postsurgery circulating serum vascular endothelial growth factor (VEGF) levels and tumor-associated macrophage (TAM) numbers, tumor VEGF expression, and other immunohistochemical parameters. A significant positive correlation was observed between the number of TAM and postsurgery circulating VEGF values (P < .05). Moreover, patients with a p53+ tumor had higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Similar to patients with hematological malignancies (31), the tumor-bearing mice in our study had significantly higher serum VEGF-A levels than their healthy counterparts. Vicioso et al demonstrated a positive correlation between the serum VEGF levels and tumor size in primary breast cancer (32). However, the serum VEGF165 levels did not correlate with tumor size in HCC (33).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to patients with hematological malignancies (31), the tumor-bearing mice in our study had significantly higher serum VEGF-A levels than their healthy counterparts. Vicioso et al demonstrated a positive correlation between the serum VEGF levels and tumor size in primary breast cancer (32). However, the serum VEGF165 levels did not correlate with tumor size in HCC (33).…”
Section: Discussionmentioning
confidence: 99%
“…As a major component of the leukocyte infiltrate of many solid tumors, TAMs are found to play a critical role in carcinogenesis, tumor growth, invasion, and metastasis, and induce tumor angiogenesis and lymphangiogenesis in different types of cancers such as non-small cell lung cancer (NSCLC) , breast cancer [Vicioso et al, 2006], malignant melanoma [Varney et al, 2005], and colorectal cancer [Bailey et al, 2007]. The effects of TAMs are related to a number of secreted proinflammatory cytokines, growth factors, chemotatic factors, and proteinases.…”
Section: Discussionmentioning
confidence: 99%
“…During breast cancer development the TAMs enhance cancer metastasis and promote resistance to chemotherapeutic agents [Gabrilovich et al, ; De Palma and Lewis, ]. Several evidence indicated that the level of high circulating VEGF was depending on the number of TAMs infiltration in primary tumor and p53 that relationship enhanced the angiogenesis in breast cancer [Vicioso et al, ]. However, the metastatic effect of VEGF and macrophage in tumor further need to the investigation.…”
Section: Tumor‐associated Macrophagesmentioning
confidence: 99%